King of Armenia’s Journey from Cairo to Barcelona: Revisiting the Social Boundaries of the Mediterranean Region in the 14th Century - Popova, Galina А. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2022)
This article raises the problem of studying the functioning of the system of social relationships that existed in the west and east of the Mediterranean region in the second half of the fourteenth century. According to the author’s assumption, the network of connections formed by the period made it possible to move within the region over considerable distances, while remaining inside the space built according to the same logic of social interactions. The issue is studied with reference to the biography of Levon V, the ruler of Cilician Armenia from the House of Lusignan. The article refers to two historical narratives written around the events described: The Chronicle of Armenia by the confessor and secretary of the king Jean Dardel and The Chronicle of King Juan I by Pedro Lуpez de Ayala. The paper also considers the question of the limits of socialisation in the case of rapid movement from one region of the Mediterranean to another. It is studied with reference to Levon V’s acquisition of senior power over three Castilian cities based on data from both narrative and documentary sources. The author demonstrates that due to the general dense network of social relationships that developed in the region, it was possible to move a very considerable distance from the southeast to the west of the Mediterranean without significant material resources, while maintaining a high social position. This was reflected in the fact that at the level of ceremonial and public gestures, the logic of the functioning of the social system was equally clear in the West and in the East. However, only a small part of society had the possibility of such spatial movement without changing or losing position.